BIOLOGY OF THE GOAT OF THE LEAF OF THE BANANA Opsiphanes envirae Hubner (Lepidoptera: Brassolidae) - PULIDO-F., JAIME; CÁRDENAS-M., REINALDO (Revista Colombiana de Entomología, 1979)
Plantain and banana crops in the Quindio area of Colombia were seriously affected by Opsiphanes envirae Felder in 1979. At least 503 ha of plantain suffered varying degrees of defoliation. The life cycle, habits, host plants, and natural enemies of this pest were studied. Observations on some bioecological aspects were made. At 23,4°C and 74,3% R.H. the egg, larval, prepupal and pupa) stages lasted 5,8; 29,8; 2,8 and 13,3 days, respectively. There are five larval instars. The main differences among them are the number and color of the caudal horns. The highest foliage consumption was recorder for fourth and fifth instar larvae. Larvae pupate in the lower part of plantain and coffee plants as well as on weeds. The pupa is kidney-shaped and bears two characteristic shiny spots. Females lived and an average of 30 days; males lived 15 days; the sexes can be distinguished by comparing the median and lateral portions of the abdomen. The highest number of eggs/female recorded was 96; average, 80,8 eggs. All eggs obtained under laboratory conditions were infertile. The average preoviposition period was 3,8 days. The Hymenoptera Ooncyrtus sp (Encyrtidae), Telenomus sp (Scelionidae), Apanteles sp (Braconidae); Spilochalcis nigrifrons (Cameron) (Chalcididae), Polistes erytrocephalus Latreille, Polistes spp (Vespidae) and the pathogen Bacillus cereus were the main natural enemies found. Besides plantain, (Musa paradisiaca L.), banana (Musa sapientum L.) and "guineo" (Musa cavendish Lamb) the pest was also found on "platanillo", (Heliconia sp.).